Dynamics of emigration : émigré scholars and the production of historical knowledge in the 20th century - Berger, Stefan; Müller, Philipp (Historian), 1974- (New York : Berghahn Books, 2022)
"As a pioneering volume to consider the impact of exile on historical scholarship in the twentieth century in a systematic and global way, looking at Europe, North America, South America and Asia, Dynamics of Emigration asks about epistemic repercussions on the experience of exile and exiles. Analyzing both the impact that exile scholars had on their host societies and on the societies they had to leave, the volume investigates exiles' pathways to integration into new host societies and the many difficulties they face establishing themselves in new surroundings. Focusing on the age of extremes and the realms of exile from fascist and right-wing dictatorships as well as communist regimes, the contributions look at the reasons scholars have for going into exile while providing side-by-side examination of the support organizations and paths for success involved with living in exile"--
Frontmatter -- Contents -- Introduction. Dynamics of Émigré Scholarship in the Age of Extremes -- Chapter 1. 'A Private Perch': Cosmopolitanism, Nostalgia and Commitment in the Émigré Historian's Persona -- Chapter 2. The Émigré Historian: A Scholarly Persona? -- Chapter 3. The Long Arm of the Dictator: Cross-Border Persecution of Exiled Historians -- Chapter 4. Nativism and the Spectre of Antisemitism in the Placement of German Refugee Scholars, 1933-1945 -- Chapter 5. Defending Objectivity: Paul Oskar Kristeller and the Controversy over Historical Knowledge in the United States -- Chapter 6. Émigré Historians and the Postwar Transatlantic Dialogue -- Chapter 7. Between Integration and Institutional Self-Organisation: Polish Émigré Scholarship in the United States, 1939-1989 -- Chapter 8. The Unlikely Careers of Laura Polanyi (1882-1959) as a Historian: The Intersections of Exile, Gender, Class and Age -- Chapter 9. 'From Geistesgeschichte to Public History': The Years of Emigration of the Hungarian Historian Béla Iványi-Grünwald, Jr. -- Chapter 10. Building New Networks: Russian Émigré Scholars in Yugoslavia -- Chapter 11. Networking in Santa Barbara, Writing History: Dimitrije Ðorđevic´ and the Comparative History of Balkan Nations -- Chapter 12. António Sérgio and José Ortega y Gasset: History, Theory and Experiences of Exile -- Chapter 13. Émigré Portuguese Historians in France, 1945-1974: New Methods of Thinking and Writing Portuguese History -- Conclusion. New Perspectives on Émigré Scholarship and What Remains to be Done -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 04, 2022).
JSTOR
Keywords: Historiography -- History -- 20th century; Historians; Exiled scholars -- History -- 20th century; Learning and scholarship -- History -- 20th century; Historiographie -- Histoire -- 20e siècle.; Savoir et érudition -- Histoire -- 20e siècle.; HISTORY / Modern / 20th Century; HISTORY / Modern / 20th Century / General; Exiled scholars; Historians; Historiography; Learning and scholarship; 1900-1999; History